2021
DOI: 10.1002/ejp.1795
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine prevented hypersensitivity and decreased oxidative stress by NMDA receptor antagonism after spinal cord injury in rats

Abstract: Background: Neuropathic pain (NP) after spinal cord injury (SCI) is a disabling condition, without an effective treatment. Hyperexcitability of N-methyl-D-aspartate (NMDA) receptors and oxidative stress have been reported to be associated with pain development. Amantadine, an NMDA receptor antagonist, has been proposed as a potential therapy for NP. However, its use has not been tested for NP after SCI. Methods: To produce SCI, 120 female Wistar rats were used, a contusion injury to the T10 and T12 thoracic ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For instance, damage to the central nervous system and the resulting increase in extracellular levels of glutamate causes excessive activation of N-methyl- D -aspartate (NMDA) receptors. This, in turn, leads to an influx of calcium ions which eventually produces large amounts of ROS ( Yang et al, 2021 , Mata-Bermudez et al, 2021 ). Altogether, these processes damage cells irreversibly and may even lead to apoptosis.…”
Section: Oxidative Stress Reactionmentioning
confidence: 99%
“…For instance, damage to the central nervous system and the resulting increase in extracellular levels of glutamate causes excessive activation of N-methyl- D -aspartate (NMDA) receptors. This, in turn, leads to an influx of calcium ions which eventually produces large amounts of ROS ( Yang et al, 2021 , Mata-Bermudez et al, 2021 ). Altogether, these processes damage cells irreversibly and may even lead to apoptosis.…”
Section: Oxidative Stress Reactionmentioning
confidence: 99%
“…75 In addition, NMDARs are present in dorsal root ganglion neurons and afferent terminals in the superficial dorsal horn. 76 Studies revealed the contribution of altered expression and/or phosphorylation of NMDAR subunits to abnormal pain processing in different conditions such as peripheral nerve injury, 77 diabetes, 78 morphine exposure 79 and excitotoxic 80 or traumatic spinal cord injuries, 30,81,82 indicating the central role of NMDAR-associated signaling pathways in the development of several types of chronic pain. In addition, studies using either antagonists or knockdown of NMDAR demonstrated reduced nociceptive behaviors and pain sensitivity caused by central or peripheral injury.…”
Section: Brief Overview Of Spinal Nmdar Function and Activity In Chro...mentioning
confidence: 99%